Impact of 7-valent pneumococcal conjugate vaccine (PVC-7) on the incidence and treatment of pneumonia diagnosed in primary care in children and adolescents in UK. (4th April 2011) - El Turki, A; Hsia, Y; Saxena, S; Long, P; Wong, I; Sharland, M
Abstract : Background: Streptococcus pneumonia is the main cause of bacterial pneumonia in children in the UK. In September 2006, a 7-valent pneumococcal conjugate vaccine (PCV7) was introduced into the UK childhood immunisation schedule following a successful campaign in the USA, where all cause pneumonia admissions in children under 2 years of age fell by 39% within 2 years. Hospital admission data in England noted reductions in pneumonia and empyema rates of around 20% in children aged 0–15 years within 2 years. However, the impact of PCV7 on the clinical burden diagnosis and antibiotic treatment of all cause pneumonia in primary care in the UK is unclear. Objective: To investigate the incidence of pneumonia and antibiotic prescribing for pneumonia in children aged 0–18 years in general practices in UK between 2002 and 2009. Methods: We used the UK IMS Disease Analyzer (IMS DA) database to construct a cohort of all children and adolescents aged 0–18 years between 1 January 2002 and 31 December 2009. We developed inclusive ICD–10 coding lists for bacterial, viral and all cause pneumonia to compare trends by age before and after the introduction of PCV-7. We used these coded data to examine annual consulting rates and antibiotic prescribing rates in children presenting with all cause pneumonia. Results: In our preliminary results, we identified 302 781 children and adolescents aged 0 to 18 years within the IMS DA database's study population between 2002 and 2009. There were 813 patients (0.3%) with a diagnosis of pneumonia. Overall, pneumonia diagnoses were stable, but there was a 35.7% decline in pneumonia consultation rates in children aged 0–18 years old between 2006 and 2009, from 2.8/1000 person-years (95% CI 2.6 to 3.1) to 1.8/1000 person-years (95% CI 1.6 to 2.0) respectively. This reduction was most marked in children aged under 2 years with a 9.2-fold decline from 8.7/1000 person-years (95% CI 7.2 to 10.1) in 2007 to 1.0/1000 person-years (95% CI 0.4 to 1.4) in 2009. Antibiotic prescribing for pneumonia in children aged under 2 years also declined from 1.3/1000 person-years (95% CI 0.7 to 1.9) in 2007 to 0.3/1000 person-years (95% CI 0.01 to 0.6) in 2009, with no similar change noted in other age groups. Conclusion: Following the introduction of PCV-7 into the UK childhood immunisation programme, there was a marked reduction in pneumonia consultations and antibiotic treatment among children aged under 2 years that was not seen in older children.